Sociologies Perspectives on Unregistered Marriages in Muslim Socities - Zed Bachmid; Malkan Malkan; Ali Imron (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2021)
The study focuses on the practical concept of the unregistered marriage at the Marawola Sub-district. It seeks to understand factors that cause the practices and their sociological impacts. The study aims to recognize the practical concept of the unregistered marriage, factors affecting the practices, and their sociological impacts. The study is a descriptive research by nature. It employs different data collection techniques while adopting qualitative approach in its data analysis. The setting of the study is at the Marawola Sub-district. The findings of the study show that there were a lot of people in the community under the authority of the Marawola Sub-district practiced unregistered marriages. They made mention that the reasons for their practices which were derived from their interviews were legal because they believed that the unregistered marriages have fulfilled terms and conditions for lawful marriages. They argued that a marriage registration is only for the legalization of the marriage. The reasons for the unregistered marriage practices covered many factors. First, it is due to the ignorance of the community in regards to procedures for a marriage registration at the Marawola Sub-district. Other reasons are related to administrative requirements for a marriage registration and marriages by accident due to pregnancies. In addition, unlawful actions of irresponsible individuals in the community who helped perpetrators to find a shortcut for the Unregistered Marriages could also cause the insurgence of the practices. These all brought sociological impacts in their society especially for wives and children where there is no legal protection for them. Hence, there was no recognition from formal law which then resulted in long-term social impacts and negative turmoil in the community.